Social Media and Elections: The Use of Twitter in the 2013 Campaigns in Italy, Australia, Germany, and Norway - Enli, Gunn; Larsson, Anders; Kalsnes, Bente; Skogerbø, Eli; Moe, Hallvard; Bruns, Axel; Highfield, Tim; Sauter, Theresa; Nuernbergk, Christian; Neubarth, Julia; et al. (AoIR Selected Papers of Internet Research, 2013)
Social media are playing an increasingly important part in political campaigning. Recent elections have seen a shift from early uses of blogs (e.g. in the 2004 US election; cf. Adamic & Glance, 2005) or bespoke candidate-centred social media campaigning and fundraising platforms (such as my.barackobama.com in the 2008 US election) towards a focus on the leading generic social media sites Facebook and Twitter. Many political candidates and party organisations now regularly develop public presences in both, but the specific affordances of these two platforms result in a differentiation of potential uses: the former is centred around strong-tie ’friend’ networks, and provides an opportunity for political operatives to establish a central point of contact which other users ’like’ and through which campaign information is disseminated; the latter is built around weak-tie follower networks and ad hoc hashtag publics (Bruns & Burgess, 2011a) in which politicians’ accounts may participate, but which do not afford a similar opportunity for them to carve out a space which they are able to control. This panel offers a comparative perspective on the use of Twitter as a campaigning tool across four elections taking place during 2013. This comparative perspective is important as much social media campaigning research to date has largely centred on the highly idiosyncratic US electioneering process; such research is unable to be translated easily to the more common Westminster or proportional election systems as they are used in the majority of Western democracies. Therefore, the panel focusses instead on national elections in Italy (February 2013), Norway, Australia, and Germany (all September 2013). Using broadly compatible methodologies, the papers in this panel build on data about the performance of and user reactions to politicians’ and candidates’ Twitter accounts from early 2013 through to the eventual September election dates (or from 1 January to 24 February 2013 for the Italian election). This is contrasted with activity patterns in the key hashtags associated with each election. The observation of activity around candidate accounts provides a number of new perspectives on election-related Twitter activities which previous work on election hashtags (e.g. Bruns & Burgess 2011b; Larsson & Moe 2011) is unable to provide: it is able - to determine the relative tweeting approaches of the different candidates, and to develop a typology of such strategies (ranging potentially from the dissemination of press releases to direct discussion and engagement with the electorate, and from carefully designed election messages to stream-of-consciousness tweeting); - to correlate such patterns with the relative electoral positioning of candidates and parties in the context of current election polls; - to trace the volume of candidates’ tweets and ordinary users’ responses and determine correlations with key campaign events (major speeches, debates, gaffes, etc.); - to identify key themes in tweet contents and trace their prevalence over time, in order to examine whether such themes align with the known political themes of the election period as they are covered by mainstream media; - and to examine the networks of interactions between the candidates themselves, between candidates and other significant political actors (journalists, lobby groups, extraparliamentary activist groups), and between candidates and the wider electorate, in order to explore the different conceptions of political communication and debate which may be at play here (ranging from interaction between privileged political actors to a more comprehensive engagement even with ’ordinary’ electors). The unique constellation of three national elections in the space of two weeks in September, preceded by the Italian election in February, offers an important opportunity to conduct such work on a comparative basis in order to evaluate the relative attention paid to Twitter as a campaigning tool across the four nations. Previous research suffers from the distance between specific election case studies, which - given the continuing rapid development of Twitter as a political tool, and the substantial ongoing growth in Twitter accounts - means that cross-national comparisons are virtually impossible. The four papers in this panel will provide such contemporaneous national comparisons for the first time. References: Adamic, L. A., & Glance, N. (2005). The political blogosphere and the 2004 U.S. election: Divided they blog. 2nd Annual Workshop on the Weblogging Ecosystem: Aggregation, Analysis and Dynamics, Chiba, Japan, 10 May 2005. Retrieved from http://www.blogpulse.com/papers/2005/AdamicGlanceBlogWWW.pdf Bruns, A., & Burgess, J. (2011a). The use of Twitter hashtags in the formation of ad hoc publics. European Consortium for Political Research conference, Reykjavík, 25-27 Aug. 2011. Reykjavík. Retrieved from http://eprints.qut.edu.au/46515/ Bruns, A., & Burgess, J. (2011b). #ausvotes: How Twitter covered the 2010 Australian federal election. Communication, Politics & Culture, 44(2), 37–56. Retrieved from http://eprints.qut.edu.au/47816/ Larsson, A.O., & Moe, H. (2011). Studying political microblogging: Twitter users in the 2010 Swedish election campaign. New Media & Society 14(5), 729-747. DOI: 10.1177/1461444811422894.